2015
DOI: 10.1007/978-3-319-24574-4_51
|View full text |Cite
|
Sign up to set email alerts
|

Liver Motion Estimation via Locally Adaptive Over-Segmentation Regularization

Abstract: Despite significant advances in the development of deformable registration methods, motion correction of deformable organs such as the liver remain a challenging task. This is due to not only low contrast in liver imaging, but also due to the particularly complex motion between scans primarily owing to patient breathing. In this paper, we address abdominal motion estimation using a novel regularization model that is advancing the state-of-the-art in liver registration in terms of accuracy. We propose a novel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Previously, we developed a method to automatically segment the diseased bowel wall from post-contrast MR images [33]. An obvious way to enhance the registration might be to give high priority to such regions [34]. However, we have found that this does not lead to a significant improvement, which we attribute to the small size of the regions.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we developed a method to automatically segment the diseased bowel wall from post-contrast MR images [33]. An obvious way to enhance the registration might be to give high priority to such regions [34]. However, we have found that this does not lead to a significant improvement, which we attribute to the small size of the regions.…”
Section: Discussionmentioning
confidence: 92%
“…Registered non-contrast-enhanced time series are manually segmented and contrast enhancements within the different tissue classes are simulated based on pharmacokinetic modeling to generate a pseudo-ground truth. A DIR that is suitable for aligning both common clinical hepatic DCE-MRI as well as longer time series was proposed by Papiez et al [ 12 ]. The method was evaluated based on manually annotated landmarks and an analysis of the deformation fields.…”
Section: Introductionmentioning
confidence: 99%
“…that the deformation field be a diffeomorphism [3]. Alternatively, in order to accurately model local deformations, a number of local structure or motion preservation models have been proposed [4][5][6]. However, the deformations within or between human organs are often highly complex and do not occur at a single spatial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Such structures and connections between them can be represented for example by a MST, which has been shown to replicate well the underlying tissue properties and structure of anatomical connectivity [8]. In contrast to recently proposed anisotropic filter [4], bilateral filter [5], and guided image filter [6] models, the proposed new regularization model implicitly extends local filter kernels to their non-local counterparts by simultaneous consideration of spatial and intensity proximity together with the connectivity of voxel-based nodes. The new MST-based model replaces the Gaussian smoothing originally incorporated in Thirion's Demons [2,3] via employing an efficient MST non-local cost aggregation algorithm [9] to perform regularization on the estimated displacement field.…”
Section: Introductionmentioning
confidence: 99%